2008
DOI: 10.1029/2008je003108
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for anomalous cloud particles at the poles of Venus

Abstract: An analysis of near‐infrared emissions on the nightside of Venus observed by the Visible and Infrared Thermal Imaging Spectrometer (VIRTIS) instrument on board Venus Express reveals anomalous cloud particles in the polar regions of Venus. These anomalous particles are found within the centers of polar vortices at both poles and are either larger or different in composition from those elsewhere in the planet. We find no persistent latitudinal variation in cloud properties at low to midlatitudes, nor do we find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…The color variations illustrate the variation of opacities at the wavelengths arising from trace species and aerosol abundances other two wavelengths, and the reverse in areas where the features appear somewhat bluish. These differences appear consistent with influences of CO contribution at 2.32 µm ), H 2 SO 4 absorption (1.74 vs. 2.2 µm (Barstow et al 2012) and cloud particle size (1.74 vs. 2.3 µm, Wilson et al (2008)) and have been identified from Venus Express data. It seems that the compositional differences do not appear to be due to local time differences.…”
Section: Ribbons or Narrow Width Wavessupporting
confidence: 69%
“…The color variations illustrate the variation of opacities at the wavelengths arising from trace species and aerosol abundances other two wavelengths, and the reverse in areas where the features appear somewhat bluish. These differences appear consistent with influences of CO contribution at 2.32 µm ), H 2 SO 4 absorption (1.74 vs. 2.2 µm (Barstow et al 2012) and cloud particle size (1.74 vs. 2.3 µm, Wilson et al (2008)) and have been identified from Venus Express data. It seems that the compositional differences do not appear to be due to local time differences.…”
Section: Ribbons or Narrow Width Wavessupporting
confidence: 69%
“…Opacity inhomogeneities due to particles with radius >3 μm at or near the cloud base (48-50 km altitudes) are believed to be responsible for such silhouettes (Grinspoon et al 1993), being consistent with the fact that they move at speeds lower than those at the cloud top (Sánchez-Lavega et al 2008). Accumulated data in these NIR windows have proved their usefulness in inferring the conditions in the middle-to-lower atmosphere (Carlson et al 1993;Taylor and Crisp 1997;Grinspoon et al 1993;Satoh et al 2009;Tsang et al 2008;Wilson et al 2008).…”
Section: Introductionmentioning
confidence: 81%
“…(3). While this changes m by 1.5 %, the obtained values for many pixels are statistically analyzed in a scatter plot (Carlson et al 1993;Wilson et al 2008). As 1.5 % errors may only slightly blur individual branches in the scatter plot (Carlson et al 1993), they therefore have little effect on the identification of branches.…”
Section: Effect Of Snr On the Cloud Size Parametersmentioning
confidence: 99%
See 2 more Smart Citations